Suicidal behavior and associated factors among holy water users at Northwest, Ethiopia, 2023: an institution based cross-sectional study - Kassahun, Gedefaw Tegegne; Addis, Fikir; Mossie, Tilahun Belete; Belete, Habte; Munie, Birhanu Mengist (Frontiers in Psychiatry, 2024)
Objective: To assess the prevalence of suicidal behavior and associated factors among holy water users at Andassa Saint George Monastery, 2023. Methods: An Institutional based cross -sectional study was conducted at Andassa Saint George Monastery from April 5 to May 5, 2023. A systematic random sampling method was utilized to select 423 study participants and Suicidal Behavior Q-R questionnaire was used to assess suicidal behavior. The data were gathered using the epicollect5 software with a face-to-face interview method then exported to SPSS- 25 for analysis. Binary logistic regression model was used and all variables in a bivariate analysis with a p-value less than 0.25 were entered into a multivariable logistic regression model, and statistical significance was declared at a p-value less than 0.05. Results: The prevalence of suicidal behavior among holy water users was 9.7 %( 95%CI: 7.1-12.4). Being female 2.632(1.206-5.748), living alone 2.52(1.06-5.97), having depression 3.03(1.32-6.99), epilepsy 3.82(1.28-11.40), diabetes mellitus 3.37(1.229-9.25), and were significantly associated with suicidal behavior. Conclusions: In this study, almost one in ten had engaged in suicidal behavior in their life time. Several risk factors for suicidal behavior were identified, including being female, living alone, having Diabetes mellitus, epilepsy and depression.